Relato técnico da apuração de DIFAL em Santa Catarina com base no convênio 52/2017 - Oliveira, Gazielle Santos; Zittei, Marcus Vinicius Moreira; Silva, Michele Braga dos Santos (Pontifícia Universidade Católica de São Paulo - PUC/SP, 2019)
This article deals with a descriptive empirical technical report that aims to verify and clarify controversial points regarding the calculation and collection of the interstate tax differential (DIFAL) in the branch of a multinational company located in Santa Catarina. To do so, it was necessary to study legislation relevant to the above, such as Convention 52 of 2017, ICMS Regulation of Santa Catarina 2001 and others, as well as reflection on organizational culture. For the implementation of the action plan, qualitative research was used, that is, the relationship between the real and the conceptual does not require statistical techniques for data development and demonstration. From the point of view of procedures, this technical report will be made based on bibliographical and documentary research. After the research and the documentary survey, some proposals were made that were suggested to Company A (matrix), in order to improve the procedure as a whole in its subsidiary (Subsidiary C). However, faced with a scenario of a company with a lean organizational culture, the process of acceptance and implementation of the proposals took time, but nevertheless, it occurred.

Este trabalho refere-se a um relato técnico empírico descritivo que tem como objetivo verificar e esclarecer pontos polêmicos no que diz respeito a apuração e recolhimento do diferencial de alíquota (DIFAL) interestadual na filial de uma empresa multinacional, localizada em Santa Catarina. Para tanto será necessário um estudo de algumas legislações pertinentes ao exposto, como por exemplo: Convênio 52 de 2017, Regulamento do ICMS de Santa Catarina de 2001 e outras que lhe darão suporte. Assim como um estudo sobre cultura organizacional. Para implantação do plano de ação será utilizado pesquisa qualitativa, ou seja, a relação entre o real e o conceitual não requer técnicas estatísticas para desenvolvimento e demonstração dos dados. Do ponto de vista dos procedimentos, este relato técnico será feito com base em pesquisa bibliográfica e documental. Após as pesquisas e o levantamento documental foram elaboradas algumas propostas que foram sugeridas a Empresa A (matriz), a fim de melhorar o procedimento como um todo na sua filial (Filial C). Entretanto, diante de um cenário de uma empresa com uma cultura organizacional enxuta, o processo de aceitação e implantação das propostas demorou, mas ainda assim, ocorreu.
Technical report of the Difal clearance in Santa Catarina based on the convention 52/2017
Keywords: Differentiation of rate; Legislation; DIFAL; Organizational culture; Legislações; Cultura organizacional; Subsidiary C; Filial C